2011
DOI: 10.1523/jneurosci.3337-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptor Signaling Modulates Permeability of the Blood–Brain Barrier

Abstract: The blood-brain barrier (BBB) is comprised of specialized endothelial cells that form the capillary microvasculature of the central nervous system (CNS) and is essential for brain function. It also poses the greatest impediment in the treatment of many CNS diseases because it commonly blocks entry of therapeutic compounds. Here we report that adenosine receptor (AR) signaling modulates BBB permeability in vivo. A1 and A2A AR activation facilitated the entry of i.v.-administered macromolecules, including large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
259
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(267 citation statements)
references
References 51 publications
(52 reference statements)
8
259
0
Order By: Relevance
“…A variety of transporters and receptors are highly expressed on brain endothelial cells that selectively restrict or allow the entry of substances, some of which are necessary for normal brain function, such as glucose and amino acids, while others are expelled (14,55). Our previous studies showed that activation of the A2A AR increases BBB permeability to entry of large molecules that is mediated by increased paracellular permeability, induced RhoA activity, and rearrangement of the actin-cytoskeleton in brain endothelial cells (44,59). However, 6, A-C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A variety of transporters and receptors are highly expressed on brain endothelial cells that selectively restrict or allow the entry of substances, some of which are necessary for normal brain function, such as glucose and amino acids, while others are expelled (14,55). Our previous studies showed that activation of the A2A AR increases BBB permeability to entry of large molecules that is mediated by increased paracellular permeability, induced RhoA activity, and rearrangement of the actin-cytoskeleton in brain endothelial cells (44,59). However, 6, A-C).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that ARmediated signaling increases the permeability of the BBB to large molecules in vivo and in vitro (44,59). In this study, to test the hypothesis that AR signaling regulates P-gp function, we used in vitro BBB models to determine whether AR signaling can indeed inhibit the expression and function of P-gp.…”
Section: P-gp Is Highly Expressed In Primary Human Brain Endothelial mentioning
confidence: 98%
See 2 more Smart Citations
“…Endothelial cells express several or all four known adenosine receptors, including A1, A2a, A2b, and A3 6. Adenosine limits the secretion of the cytokines IL‐6 and IL‐8 by acting on A2A receptors 7. Adenosine also prevents the increase of vascular permeability, and thus promotes endothelial barrier integrity 7.…”
Section: Introductionmentioning
confidence: 99%